The Crime Analyst's Companion - Bland, Matthew; Ariel, Barak; Ridgeon, Natalie (Cham : Springer International Publishing : Imprint: Springer, 2022)
This volume presents a collection of essays from experienced crime analysts from around the world. It explores global themes relevant to anyone embarking on, or already into a career in crime analysis or law enforcement. Divided into two sections, this book addresses technical issues central to the profession, from collection of data to presenting findings to reluctant audiences. It incorporates a collection of methodological case studies, demonstrating the ways analysis has made a meaningful difference to policing and security.
1. An introduction to crime analysis -- 2. Why does a crime analyst need a companion? -- Part I. The Crime Analysis Profession -- 3. Different types of crime analyst? -- 4. Crime analysis in an international context -- 5. The role of crime analysis in evidence-based policing -- 6. Building the analyst you want to be -- 7. Analysts from a Police Commander's perspective -- 8. The literature on Crime Analysis -- Part II. Techniques for Crime Analysis -- 9. An overview of analytical techniques -- 10. Constructing a question and shaping an answer -- 11. An overview of GIS in policing -- 12. The development of a new capability: geographic profiling analysis in Australia -- 13. Integration of geographic profiling with forensic intelligence to target serial crime -- 14. Working on major crime investigations -- 15. Crime harm indices -- 16. Problem solving and SARA -- 17. Analysing descriptive results -- 18. Algorithms -- 19. Reports and data visualisation -- 20. Statistics for analysts -- 21. Criminological theories for analysts -- 22. Landing your recommendations -- 23. Partnering with police -- 24. Dealing with difficult cops -- Part III. Analysts making a difference in Law enforcement decision making: case studies -- 25. Geo profiling -- 26. Major crime -- 27. Targeting analysis -- 28. Algorithm -- 29. Evaluation -- 30. Implementing evidence: developing data analysis as a sustainable capability -- Part IV. Conclusions -- 31. The future of the role -- 32. Concluding thoughts.
Keywords: Criminology; Forensic sciences; Crime Control and Security; Research Methods in Criminology; Forensic Science